Starting from Kerbung and Ending in Pesantren: The Analysis of the Track Record of the Emergence of Pesantren in Lombok - Murdianto (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2021)
The people of Lombok have recognized the term of Kerbung prior than Pesantren (Islamic Boarding School). Kerbung was the Islamic boarding school (hereafter pesantren) of Lombok’s Society. However, both Kerbung and Pesantren are Islamic educational institutions rooted in the history and culture of Indonesia. The track record of the emergence of Pesantren in Lombok was associated with the revival of Islam in the late 19th century. It was marked by the growth of recitation centers, as can be found in Pagutan, Kediri, Batubangka Sakra, Praya, Sesela, Sekarbela and Tanjung (East Lombok). Besides, more than 2000 intellectual works of Lombok's Muslims were also found at that time. Some of these manuscripts were used as references by the tuan guru for their students. This research is field research with a qualitative paradigm. This study found that the track record of the emergence of pesantren in Lombok was an integration of the Islamic educational system in Lombok, Java and the Middle East. However, the emergence of pesantren in Lombok was inseparable from the founding fathers of the pesantren itself.